Давньоруська державність як метанаратив - Виноградов, Г. (Інститут історії України НАН України, 2008)
The article is dedicated to the characteristics of the Ancient Rus’ Statehood as a artificial symbolic construction o n the base of the medieval mental principles. Special attention is paid to analysis of the linguistic revolution in the new intellectual historiography concerning the ‘Pax Slavia Orthodoxa’ and the Ancient Rus’ medieval period especially first time in the contemporary slavistics.